Significance of acetogenic H-2 consumption in dark fermentation and effectiveness of pH - ÇALLI, BARIŞ (IWA PUBLISHING, 2008)
Two identical thermophilic H-2 fermenters (R1 and R2) were operated at different pH levels between 4.7 and 5.7. In R1, several unexpected and severe drops in H-2 yield inversely proportional to increase in acetate production were experienced at pH 5.5 and 5.7. In contrast, R2 operated at pH 5and 4.7 performed more stable H2 production mainly through butyrate fermentation. Although the H-2 partial pressure (> 50 kPa) was far above the favorable values, acetate was produced as well as butyrate in all pH levels tested. To determine whether some portion of the acetate is produced through another pathway such as autotrophic synthesis via H-2 dependent reduction of CO2 or not, batch dissolved H-2 consumption rate tests were performed at pH 5.0, 5.5 and 6. The specific H-2 consumption rate was 488(+/- 49) mu mol/gVSS.hr at pH 6 and slightly higher than at pH 5and 5.5. The results of continuous and batch experiments revealed that acetogenic H-2 consumption is more favorable at pH levels above 5.5 and is one of the reasons of instabilities in dark fermentative H-2 production.
Keywords: acetogenesis; dark fermentation; dissolved hydrogen; mixed culture; thermophilic; PROPIONIC-ACID ACCUMULATION; BIOHYDROGEN PRODUCTION; HYDROGEN